Case report of venous air embolism in complete placenta previa in a case of lower segment caesarean section - Noureddine, Korichi; Ramanathan, Lakshmi; Thode, Aboobaker; Vijyakumari, Vipin Reghunatan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Thromboembolic episodes in the pregnant and postpartum period in patients remain rare but fatal causes of maternal morbidity and mortality. They can be either venous air embolism, venous thrombo-embolism which include deep vein thrombosis and pulmonary embolism and last but not the least amniotic fluid embolism. The incidence of embolic episodes is more in LSCS patients than in patients coming for normal vaginal deliveries for all the type of embolisms, ranging from 10-97% for air embolisms depending on the surgical position and diagnostic tools with a potential for life threatening events, for venous thromboembolism (VTE) it is 0.5-2.2% patients per 1000 deliveries and increased 5-10-fold in pregnancy and 15-35% in postpartum period as compared to the non-pregnant women, the highest being during the 1st 3-6 weeks postpartum. After that the risk declines rapidly, although a small risk increase persists up to 12 weeks. After delivery, incidence of pulmonary embolism ranges from 0.11-0.73% per 1000 deliveries. It is rare, unpredictable, and unpreventable life-threatening complication of pregnancy. According to the International Cooperative Pulmonary Embolism registry, the death rate from massive PE among hemodynamically unstable patients is 52%. Last but not the least, incidence of amniotic fluid embolism ranges from 1/8000 to 1/15000. Delayed diagnosis, delayed treatment or inadequate treatment and inadequate thromboprophylaxis account for many of these deaths. Hence, early detection and proper management helps to prevent maternal mortality and morbidity in our patients. Also, thrombotic prophylaxis helps in preventing the fatal outcome and morbidity and mortality in our patients. Here, we report a case of a patient with complete placenta Previa scheduled for elective Lower segment caesarean section who developed venous air embolism (VAE) but with prompt detection and treatment a fatal outcome was prevented.